2016
DOI: 10.18203/2320-1770.ijrcog20164637
|View full text |Cite
|
Sign up to set email alerts
|

A study of vitamin D levels and associated deficiency in pregnancy and its effect on maternal and fetal outcome

Abstract: Background: From conception the embryo is dependent on the mother for all nutritional requirements until birth. Vitamin D deficiencies have adverse effect on pregnancy outcome result in poor growth, prematurity, NTD, even congenital anomalies. The aim and objectives of the study was to assess the prevalence of deficiencies among pregnant woman attending M.Y. Hospital and assess the correlation with the pregnancy complications.Methods: Total 110 patients were studied for vitamin d levels and associated obstetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…5 Vitamin D deficiency was significantly higher in subjects who were less exposed to the sunlight (99.62%). Similar results were there in the study conducted by Dave A et al, and Prasad D et al 8,9 Adequate exposure to the sunlight is essential for vitamin D production in our body and is markedly decreased in winters.…”
Section: Discussionsupporting
confidence: 87%
“…5 Vitamin D deficiency was significantly higher in subjects who were less exposed to the sunlight (99.62%). Similar results were there in the study conducted by Dave A et al, and Prasad D et al 8,9 Adequate exposure to the sunlight is essential for vitamin D production in our body and is markedly decreased in winters.…”
Section: Discussionsupporting
confidence: 87%
“…(Table 4) The mean age observed among the cases was 24.9±3.5 years and Vitamin D deficiency was more when the age was greater than and equal to 30 years (84.6%) when compared the population less than 30 years (65.4%). Goel P et al (2016) observed that the mean age among women with hypertensive disorders of pregnancy was 25.48 years and that 83.3% of those subjects were Vitamin D deficient [10] Dave A et al (2017) observed that pregnant women below 30 years of age had higher odds of developing deficiency of Vitamin D compared to the older population [8]. The sunlight exposure was also considered based on the whether the woman's occupation involved outdoor (more exposure) or indoor (less exposure) work.…”
Section: Discussionmentioning
confidence: 99%
“…Obsgyne Review: Journal of Obstetrics and Gynecology Available online at: www.medresearch.in 22 | P a g e pregnancy [7]. But on the contrary Anupama Dave et al (2016) felt that there was no causal relationship between low vitamin D level and adverse maternal and neonatal outcome in terms of hypertension, anaemia, caesarean section rates, diabetes or bony pain [8]. Hence an effort was made to establish the relationship between serum level of vitamin D in hypertensive disorders in pregnancy and if a correlation exists between the serum level of vitamin D and the severity of hypertensive disorder in pregnancy.…”
Section: Original Research Articlementioning
confidence: 99%
“…Merewood et al, study showed vitamin D deficiency has been associated with four-fold increased risk of primary caesarean section although this is not supported by all studies. 2 Dave et al, shows an association of vitamin D deficiency and caesarean deliveries 23.5% delivered by cesarean had vitamin D deficiency but this was not statistically correlated. 1 In this study 34.5% in deficiency, 18.2% in insufficiency had undergone primary caesarean section.…”
Section: Discussionmentioning
confidence: 94%
“…25(OH)D is the main circulating vitamin D metabolite and its serum level serves as a biomarker of the vitamin status. 2 High risks are vegetarians, limited sun exposure and ethnic minorities. Vitamin D (25 hydroxy D) is measured, normal 30 ng /ml.…”
Section: Introductionmentioning
confidence: 99%